Improving CPR Quality by Using a Real-Time Feedback Defibrillator During Pediatric Simulation Training. Issue 2 (February 2022) - Frazier, Maria; Dewan, Maya; Keller-Smith, Rachel; Shoemaker, Jamie; Stewart, Claire; Tegtmeyer, Ken
Abstract : Objective: The aim of this study was to assess the effectiveness of a defibrillator with real-time feedback during code team training to improve adherence to the American Heart Association (AHA) resuscitation guidelines. Methods: This is a retrospective cohort study designed to compare pediatric resident adherence to the AHA cardiopulmonary resuscitation guidelines before and after use of real-time feedback defibrillator during code team training simulation. After institution of a real-time feedback defibrillator, first-year resident's adherence to the AHA guidelines for chest compression rate (CCR), fraction, and depth during code team training from January 2017 to December 2018 was analyzed. It was then compared with results of a previously published study from our institution that analyzed the CCR and fraction from January 2015 to January 2016, before the implementation of a defibrillator with real-time feedback. Results: We compared 19 eligible session preintervention and 36 postintervention sessions. Chest compression rate and chest compression fraction (CCF) were assessed preintervention and postintervention. The depth of compression was only available postintervention. There was improvement in the proportion of code team training sessions with mean compression rate (74% preintervention vs 100% postintervention, P = 0.003) and mean CCF (79% vs 97%, P = 0.04) in adherence with the AHA guideline. Conclusions: The use of real-time feedback defibrillators improved the adherence to the AHA cardiopulmonary resuscitation guidelines for CCF and CCR during pediatric resident simulation.